Determinants of attitude towards information and communication technology usage among rural administrators in using Structural Equation Modelling - D'Silva, Jeffrey Lawrence; Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril; Abu Hassan, Musa; Badsar, Muhamad (Science Publications, 2011)
Problem statement: Village Development and Security Committee members play a vital role in enhancing the village development programs in Malaysia and ICT is deemed as an important mechanism to further boost rural development. But do the rural community in Malaysia especially their leaders have a positive attitude towards it? Hence, this study is designed to identify the constructs that significantly influence the attitude of Village Development and Security Committee members in using ICT. Approach: This is a quantitative study where a total of 240 respondents have been selected based on the stratified random sampling done. AMOS and SPSS were used to gain the required analyses. Results: The structural equation modelling showed that there were three constructs that significantly predict the attitude and these constructs were perceived ease of use, perceived usefulness and job relevance. Conclusion/Recommendation: It is recommended that more technology investment in the form of providing ICT facilities and trainings should be made by the government to encourage the development of a positive attitude among VDSC members. The findings of this study would be useful for policy makers to further boost the usage of ICT in rural areas.